Управління витратами в системі економічної безпеки підприємства - Ларка, Людмила Сергіївна; Ковтун, Дар'я Сергіївна; Гордієвська, Альона Ігорівна (My University, 2020)
Досліджено проблему забезпечення економічної безпеки підприємства у взаємозв’язку із проблемами планування, управління витратами, розроблення систем моніторингу. Актуальність дослідження зумовлюється необхідністю виявлення резервів підвищення ефективності діяльності підприємства за рахунок удосконалення системи економічної безпеки. Метою статті є розвиток теоретико-методичних засад управління витратами в системі економічної безпеки підприємства. Обґрунтовано доцільність класифікації витрат підприємства за ознакою фінансування складників системи економічної безпеки. Визначено склад витрат за фінансовою, кадровою, технічною, правовою, екологічною, інформаційною та ринковою складовими частинами системи економічної безпеки підприємства. Визначено ризики недофінансування складових частин системи економічної безпеки підприємства.

The problem of ensuring the economic security of an enterprise in connection with the problems of planning, cost management, and the development of monitoring systems has been investigated. The relevance of the study is determined by the need to identify reserves for increasing the efficiency of the economic activity of the enterprise by improving the system of economic security. The purpose of this article is to develop theoretical and methodological principles of cost management in the system of economic security of the enterprise. The objectives of the article are to develop a classification of costs of the enterprise on the basis of place in the system of economic security of the enterprise, specify their composition and determine the risks of underfunding of the components of economic security of the enterprise. The expediency of classifying the costs of the enterprise on the basis of financing the components of the economic security system is substantiated. The composition of costs for financial, personnel, technical, legal, environmental, informational and market components of the enterprise's economic security system has been determined. The risks of underfunding of the components of the economic security system of the enterprise are determined. The consequences of underfunding the elements of the economic security system of the enterprise are systematized, which are manifested in an increase in staff turnover, a decrease in the market segment, a deterioration in the reputation of an enterprise and a loss of competitive advantages. Areas for improving the management of costs for economic security of the enterprise are: increasing the degree of justification of the need for funding for the main components of the economic security system; uniform financing of the main components of the economic security system, without artificial overestimation of the significance of individual components of the system; analysis of the development of allocated funding for targeted use of funds. Allocation of the content of costs for the main components of economic security allows to minimize the risks of their financing in an insufficient amount.
Keywords: економічна безпека; фінансова безпека; витрати; управління; система; підприємство; economic security; financial security; management; system; enterprise